2019
DOI: 10.1088/1748-605x/aafbf1
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid core–shell scaffolds for bone tissue engineering

Abstract: The tissue engineering applications of coaxial electrospinning are growing due to the potential increased functionality of the fibres compared to basic electrospinning. Previous studies of core and shell scaffolds have placed the active elements in the core, however, the surface response to a biomaterial affects the subsequent behaviour, thus here hydroxyapatite (HA) was added to the shell. Coaxial electrospun polycaprolactone (PCL)-polylactic acid (PLA)/HA (core–shell) scaffolds were produced in 2D sheets usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 37 publications
(37 reference statements)
0
19
0
Order By: Relevance
“…This led to a distinctive osteoclastic differentiation as well as to a reduced immunogenic effect by magnesium hydroxide, and a better mechanical and physiological response induced by the PLGA/calcium phosphate composite. The processing of the starting polymer was shown to be critical in inducing specific outcomes for the plated cells, as shown by Kareem and colleagues [153]. They have found that a core-shell electrospinning to fabricate a PCL/PLLA scaffold with hydroxyapatite particles allowed an osteoconductive environment and also induced differentiation of human mesenchymal stem cells (hMSCs).…”
Section: Bioscaffolds For Cell Cultivation In Vitromentioning
confidence: 94%
“…This led to a distinctive osteoclastic differentiation as well as to a reduced immunogenic effect by magnesium hydroxide, and a better mechanical and physiological response induced by the PLGA/calcium phosphate composite. The processing of the starting polymer was shown to be critical in inducing specific outcomes for the plated cells, as shown by Kareem and colleagues [153]. They have found that a core-shell electrospinning to fabricate a PCL/PLLA scaffold with hydroxyapatite particles allowed an osteoconductive environment and also induced differentiation of human mesenchymal stem cells (hMSCs).…”
Section: Bioscaffolds For Cell Cultivation In Vitromentioning
confidence: 94%
“…There are about a hundred published release studies with BMP-2 every year. In many cases, the release studies are carried out in PBS without any solubility increasing additives [9][10][11][12][13][14][15][16]. However, there are only a few publications that refer to the low solubility of the protein and the associated potential influence, both on the release itself (violation of sink conditions), and on the quantification of the partially aggregated protein [17].…”
Section: Introductionmentioning
confidence: 99%
“…The 3D printing technique is based on a controlled dispensing system integrated with pumping technology and a CAD/CAM system allows the precise and reproducible fabrication of 3D structures with well-defined predetermined geometries 3D printed PLA-based scaffolds. PLA emergence in 3D printing technology led to development of scaffolds in desired shapes and forms, in low cost, with corresponding mechanical and biological properties and controlled micro/nano structures [ 172 , 173 ].…”
Section: Pla Applicationsmentioning
confidence: 99%
“…The results in situ showed a decrease in postsurgical inflammation, to avoid infection and reduce the incidence of secondary cataract while having a programmed release of quantity and release profiles to cut down the need of eye drops in order to prevent inflammation or infection and to decrease the posterior capsular opacification following cataract surgery [ 221 ]. PLA, nHA and Eudragit produced double-layer microspheres were loaded with human insulin-like growth factor 1, and the results provide a promising therapeutic suggestion in order to delay osteoporosis and articular degeneration [ 172 , 222 ]. Rhodamine B as a model drug substance was loaded into PLA microchamber arrays that were prepared by dip-coating a PDMS stamp into PLA.…”
Section: Pla Applicationsmentioning
confidence: 99%